Pathologic changes in neuronal intranuclear inclusion disease are linked to aberrant FUS interaction under hyperosmotic stress - Hui Wang; Yilei Zheng; Jiaxi Yu; Lingchao Meng; Wei Zhang; Daojun Hong; Zhaoxia Wang; Yun Yuan; Jianwen Deng (Neurobiology of Disease, 2024)
CGG repeat expansion in NOTCH2NLC is the genetic cause of neuronal intranuclear inclusion disease (NIID). Previous studies indicated that the CGG repeats can be translated into polyglycine protein (N2CpolyG) which was toxic to neurons by forming intranuclear inclusions (IIs). However, little is known about the factors governing polyG IIs formation as well as its molecular pathogenesis. Considering that neurogenetic disorders usually involve interactions between genetic and environmental stresses, we investigated the effect of stress on the formation of IIs. Our results revealed that under hyperosmotic stress, N2CpolyG translocated from the cytoplasm to the nucleus and formed IIs in SH-SY5Y cells, recapitulating the pathological hallmark of NIID patients. Furthermore, N2CpolyG interacted/ co-localized with an RNA-binding protein FUS in the IIs of cellular model and NIID patient tissues, thereby disrupting stress granule formation in cytoplasm under hyperosmotic stress. Consequently, dysregulated expression of microRNAs was found both in NIID patients and cellular model, which could be restored by FUS overexpression in cultured cells. Overall, our findings indicate a mechanism of stress-induced pathological changes as well as neuronal damage, and a potential strategy for the treatment of NIID.